Biocompatible Mesoporous Silica–Polydopamine Nanocomplexes as MR/Fluorescence Imaging Agent for Light-Activated Photothermal–Photodynamic Cancer Therapy In Vivo - Lu, Jiahui; Ni, Chen; Huang, Jie; Liu, Yawen; Tao, Yingkai; Hu, Pengcheng; Wang, Yong; Zheng, Shaohui; Shi, Meilin (Frontiers in Bioengineering and Biotechnology, 2021)
Conventional cancer phototherapy with single modality suffers from low therapeutic efficacy and undesired posttreatment damage for adjacent normal tissues. Therefore, the lower NIR laser irradiation power is vital to the reduction or preclusion of risk of scalds and burns in normal tissues. Herein, we rationally proposed a novel multifunctional nanocomplex, which enabled good magnetic resonance (MR) imaging contrast effect and promising photothermal conversion efficacy. The prepared core/shell nanocomplexes [MSN-Ce6@PDA (Mn)] were composed of chlorin e6-embedded mesoporous silica/nanoparticle composites as the cores, and then polydopamine and manganese ions were conjugated on the cores to form protective shells. The MSN-Ce6@PDA (Mn) nanocomplexes revealed superior properties in colloidal stability, photothermal conversion, reaction oxygen species generation, magnetic resonance imaging, etc. Under the guidance of MR and fluorescence imaging, these MSN-Ce6@PDA (Mn) nanocomplexes were found to be primarily accumulated in the MDA-MB-231 tumor area. Furthermore, the combined photodynamic and photothermal therapy exhibited strong inhibition to the growth of MDA-MB-231 tumor in vitro and in vivo. Besides, the MSN-Ce6@PDA (Mn) nanocomplexes also exhibited excellent biocompatibility and low damage to the healthy animals. Hence, the results demonstrated that the prepared MSN-Ce6@PDA (Mn) nanocomplex would be a promising potential for multimodal imaging-guided phototherapy.